2006
DOI: 10.1038/oby.2006.251
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Fat Diet Has a Tissue‐Specific Effect on Adiponectin and Related Enzyme Expression

Abstract: BARNEA, MAAYAN, AVI SHAMAY, ALIZA H. STARK, AND ZECHARIA MADAR. A high-fat diet has a tissue-specific effect on adiponectin and related enzyme expression. Obesity. 2006;14:2145-2153. Objective: This study was designed to test whether adiponectin plays a role in diet-induced obesity and insulin resistance and acts as a mediator to induce or inhibit specific metabolic pathways involved in lipid metabolism Research Methods and Procedures: Forty C57BL/6J male mice were fed either a high-fat (HF) or control diet fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
50
6
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 34 publications
27
50
6
2
Order By: Relevance
“…By contrast, AdipoR1 mRNA expression was enhanced in skeletal muscle while AdipoR2 mRNA was not significantly changed (Figure 4a,b). These results are consistent with previous studies that found a tissue-specific effect of lipid oversupply on adiponectin response and adiponectin receptors expression (21,27,31,32). It has been shown that insulin represses adiponectin receptor mRNA expression in both muscle and liver via activation of phosphatidylinositol 3-kinase and inactivation of Foxo1.…”
Section: Articles Integrative Physiologysupporting
confidence: 83%
See 2 more Smart Citations
“…By contrast, AdipoR1 mRNA expression was enhanced in skeletal muscle while AdipoR2 mRNA was not significantly changed (Figure 4a,b). These results are consistent with previous studies that found a tissue-specific effect of lipid oversupply on adiponectin response and adiponectin receptors expression (21,27,31,32). It has been shown that insulin represses adiponectin receptor mRNA expression in both muscle and liver via activation of phosphatidylinositol 3-kinase and inactivation of Foxo1.…”
Section: Articles Integrative Physiologysupporting
confidence: 83%
“…It has been shown that insulin represses adiponectin receptor mRNA expression in both muscle and liver via activation of phosphatidylinositol 3-kinase and inactivation of Foxo1. In contrast, other studies have shown a positive correlation between serum insulin levels and AdipoR1 expression in skeletal muscles (21). High-insulin levels in LE-treated rats observed here, may affect adiponectin receptor expression uniquely in different tissues.…”
Section: Articles Integrative Physiologycontrasting
confidence: 52%
See 1 more Smart Citation
“…Although fasting glucose levels were significantly elevated in WT-HFD compared with WT-RD mice, the insulin sensitivity assessed by Quicki did not significantly differ between the two groups. An experiment using male C57BL/6J mice in experimental settings (age of mice and duration of the experiment) similar to the present study demonstrated that a high fat diet induced obesity with a significant reduction of Adipoq mRNA in the WAT while not affecting the plasma Adipoq (Barnea, 2006). The calories from fat in the HFD in the present study were 36%, whereas this was 42% in the study reported by Barnea.…”
Section: Gene Expression In Wat Associated With Energy Metabolismsupporting
confidence: 73%
“…In rodents, adiponectin peaks in the end of the light phase (inactive phase) and its rhythm is shifted under HFD (Ríos-Lugo et al 2010). Bullen and colleagues showed decreased adiponectin levels relative to fat mass following HFD in rodents (Barnea et al 2006, Bullen et al 2007. To assess the effect of adiponectin on the circadian clock, Hashinaga and colleagues used KK-Ta mice, a polygenic model of metabolic syndrome with hypoadiponectinemia.…”
Section: Leptin and Adiponectinmentioning
confidence: 99%